Implementation of Multicultural Values in Student Character Education Learning in junior high school Land 3 Pangangkajene sidrap - Muh. Fitrah; Suredah Hamid; Andi Fitriani Djollong (Universitas Muhammadiyah Palu, 2026)
his research is a study of understanding and implementation of multicultural values in secondary education institutions. The background of this study is based on the importance of strengthening wasathiyah Islamic values in response to the dynamics of diversity and potentially disorientation among students. The research focus was directed on three main aspects, namely: (1) the concept of multicultural values in an institutional context, (2) implementation of multicultural values in education practice, whether sacrificial, purification, and extracurricular activities, and (3) the implications of student values. The purpose of this study is three namely (1) to Learn how the concept of multicultural values in Islamic education in State Junior High School 3 Bangkajene sidrap (2) To Understand How implimentasi values in Islamic Education at 3 Bangkajen (impilikasi) to determine the implementation of State Islamic Education. This research used a qualitative approach with the survai method. The data was obtained through observations, interviews, and documentation, which were later analyzed using the content analysis technique (content analysis). Theological approach is used to examine the principles of Islamic wasathiyah as a normative basis of multicultural values concepts, as well as an analysis knife of education practices in the institution under study. The results showed that the secondary education institution has integrated systematic values in education policies and practices, even though in the implementation level in the field there are still several aspects that have not been implemented optimally. Values like tolerance, equality, social justice, mutual respect, intercultural dialogue, empathy and inclusion are internalized in learning activities and the life of everyday school. Implementation of positive multicultural values has a positive impact on students in three main realms: cognitive (moderate religious understanding), affirmative (inclusive and empathetic attitudes), and psychomotor (harmonious and social behavior tolerant). This study confirms the importance of the role of educational institutions in forming the character of a religious, moderate, nationality, honest and responsibility.